2016
DOI: 10.1039/c6cp05781k
|View full text |Cite
|
Sign up to set email alerts
|

Solvent effects on ion–receptor interactions in the presence of an external electric field

Abstract: In this work we investigated the influence of an external electric field on the arrangement of the solvent shells around ions interacting with a carbon-based receptor. Our survey reveals that the mechanism of interaction between a monoatomic ion and a π-type ion receptor varies by the variation in the solvent polarity, the nature of the ion, and the strength of the external field. The characteristics of the ion-surface interaction in nonpolar solvents are similar to those observed in a vacuum. However, in wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 100 publications
(124 reference statements)
2
14
0
Order By: Relevance
“…The interaction strength between Na + (H 2 O) 6 and GO becomes enhanced by increasing the negative electric field, whereas a positive electric field causes a reduction of the interaction strength. The variation is comparable to that of a previous study of the variation of the cation–graphene interactions under external electric fields. Our results demonstrate that an external electric field can modulate the adsorption interaction between hydrated Na + and the GO surface.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…The interaction strength between Na + (H 2 O) 6 and GO becomes enhanced by increasing the negative electric field, whereas a positive electric field causes a reduction of the interaction strength. The variation is comparable to that of a previous study of the variation of the cation–graphene interactions under external electric fields. Our results demonstrate that an external electric field can modulate the adsorption interaction between hydrated Na + and the GO surface.…”
supporting
confidence: 88%
“…An external electric field with controllable direction and strength has been recognized as a reversible switch to modify the ion–graphene interaction. It has been reported that the electron structure of graphene can be polarized by the external electric field, which induces the charge transfer of the ions/graphene complexes and influences the interaction between ions and graphene surfaces. In the ion–graphene systems, the field-dependent electrostatic interaction can be generally applied to explain the fundamental mechanism. , Previous study also showed that the external electric field can remotely control the activity of anion−π catalysts through the polarization of the π-system.…”
mentioning
confidence: 99%
“…From the point of view of a neuron growing on its top, MLG appears as a SLG film layered on the underlying, electrically conductive, MLG. In our hypothesis, graphene efficiency in trapping K + ions is tuned or influenced by the electronic properties of the supporting structure [42,43].…”
Section: Substrate Modulation Of Graphene Cation-π Interactionmentioning
confidence: 92%
“…The interaction energies computed using a triple‐zeta polarized Slater‐type basis set from the ADF library follow the same trends as the bond dissociation energies in Table . Analysis of the ZR‐EDA energy components unveils some general trends: 1) in all cationic complexes the orbital interaction is large, and for nonpolar graphane flakes it is the dominant energy component; and 2) among anionic systems, fluoride complexes benefit from the electrostatic term far more than their chloride and bromide counterparts, yet the orbital interaction is the main driving force for bond formation . ZR‐EDA reveals that the interplay between orbital interaction energy, electrostatics, and Pauli repulsion is responsible for the observed trends in the anion and cation affinities of G‐FF and G‐MeMe (see Supporting Information for description).…”
Section: Resultsmentioning
confidence: 94%
“…Although the importance of non‐electrostatic factors in intermolecular systems has been appreciated before, anti‐electrostatic ion–molecule interactions have not been reported to date. Note that the possibility of the formation of anti‐electrostatic intermolecular interactions has been a topic of hot debate recently .…”
Section: Resultsmentioning
confidence: 99%